Analisis Neraca Air Lahan Sawah pada Daerah Irigasi Carawali di Kabupaten Sidenreng Rappang - Nurul Anugrah AN; Reza Asra; Trisnawaty AR (Jurnal Galung Tropika, 2026)
Water balance analysis is one approach in evaluating the balance between water avaibility and water need in rice fields in an irrigation area. This study aims to determine the avaibility of irrigation Area, carawali Village, Watang Pulu District, which is the area with the largest rice field are in the region, and took place from Febrary to June 2025. The method used is a quantitive mothed, with several analytical approaches, including analysis of the mainstay discharge with the Weibull approach, calculation of water needs using the Penman Modification FAO method, water balance analysis with a water balance approach, and evaluation of irrigation netwotk afficiency using Microsft Excel. The data used consist of irrigation discharge data, rainfall, climatology, cropping patterns, and irrigation network schemes for the period 2017-2024. The results of the study showed thet water surplus condition occurred in the November-Januari (II) and April-June (II) periods, while water deficits occurred in February-April (I) and July-October (II) which reflects the inability of water avaibility to meet needs due to low rainfall and irrigation discharage.